Residue levels of enrofloxacin and ciprofloxacin in processed animal by‐products used in Atlantic salmon feeds and their long‐term carry‐over to the edible part of the fish. (23rd April 2014) - Berntssen, M.H.G.; Valdersnes, S.; Lunestad, B.T.; Hatlen, B.; Alm, M.; Waagbø, R.; Buttle, L.
Abstract Residue levels of the antibacterials enrofloxacin and ciprofloxacin were analysed in 15 commercially relevant animal by‐products (ABPs). Enrofloxacin was detected in all ABPs, and ciprofloxacin was detected in 11 of 15 ABP samples. Feed to muscle and skin carry –over of low background enro‐ and ciprofloxacin levels were assessed by applying a simple toxicokinetic model. The muscle and skin uptake and elimination rates were established in Atlantic salmon (Salmo salar L.) fed enrofloxacin enriched diets (100 μg kg−1 'low' and 4000 μg kg−1 'high') in triplicate for 41 days followed by a 90 days depuration period. The terminal half‐lives were 17 ± 0.4 and 18 ± 0.7 days, and uptake rates were 9.3 ± 3.3 and 11 ± 3.1 (day−1) for the 'low' and 'high' groups, respectively. Only fish fed high background levels had quantifiable levels of the metabolite ciprofloxacin with a formation of 0.25 ± 0.01% day−1. The toxicokinetic carry‐over model predicted muscle and skin steady state levels of 1.8 μg kg−1 when fed theoretically high enrofloxacin levels (158 μg kg−1), which is below the EU limit of 100 μg kg−1 for enrofloxacin in finfish food products. The antibacterial residue levels could however be detected in EU food surveillance programmes.